(3CQHYhf MOjkKG aj EUWfGY GdeYQhas - (3YHO GdYXje Hf YHO Gdbhj Hf YHO Gddg, CHh eMeO, Rcj GdOjf GdefPQj ,J (B656 (3g` s ((3MSf Hf egOi GdegdG s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdefPQi ELGRI , bGd (B: (3PcQJ GdeGQOjfi HGdMOjK Ef ddg JYGdi YHGOkG Ndbge Gd MhGFL GdeSdejf aSQ Hg hCeQfi Cf CJHY gPG GdHGH aNQLfJ CQHYjf MOjKkG ai EUWfGY GdeYQha s
(3BNQgG (B:s
(3GdMOjK GdCQHYhf hef eTi eY eXdhe jYjfg KHJ Gddg bOejg jhe JRd GdCbOGe hef ca ZVHg SJQ Gddg YhQJg hEf GdNdb GdSF jaSO GdYed ceG jaSO GdNd GdbJd JeJ GdCMGOjK HMeO Gddg hefg s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdSejcs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B30s
Keywords: (3GdMOjK h GdeUWdMs